Suhaveshwar Temple to the west of the Menali stream - Temples of India Project Team (Jio Institute, 2024)
The group of temples in Menal consists of two temple complexes, of which the Suhaveshwar temple complex is situated to the west of the Menali stream, a little away from the Mahanaleshwar temple complex. It is smaller in comparison to the Mahanaleshwar temple complex. It consists of a matha or monastic establishment, the Suhaveshwar Temple, and a Nandi mandapa (pillared hall). All these structures are enclosed by a prakara (compound) which has survived partially.